Areas of the European Ecological Network Natura 2000 in Roztocze - Wioletta Kałamucka; Krzysztof Kałamucki; Małgorzata Stanicka (Barometr Regionalny, 2015)
The Natura 2000 network includes Special Areas of Conservation SACs (habitat refuges coded PLH ) and Special Protection Areas SPA (bird refuges coded PLB). The objective of the network, covering the member states of the European Union, is the preservation of natural habitats and plant and animal species threatened with extinction on a European scale, as well as typical, commonly occurring natural habitats. Currently in Poland the Natura 2000 network covers almost 1/5 of the land surface. It includes 849 Sites of Community Importance (“habitat” areas — potential special areas of habitat conservation), and 145 special protection areas for birds. The region of Roztocze includes, entirely or in part, three bird refuges (PLB060012 Roztocze, PLB060008 Puszcza Solska, PLB060021 Dolina Sołokiji ) and 12 habitat refuges (PLH060070 Borowa Góra, PLH060003 Debry, PLH180017 Horyniec, PLH060089 Minokąt, PLH060017 Roztocze Środkowe, PLH060020 Sztolnie w Senderkach, PLH060022 Święty Roch, PLH060094 Uroczyska Lasów Adamowskich, PLH060034 Uroczyska Puszczy Solskiej, PLH060093 Uroczyska Roztocza Wschodniego, PLH060028 Zarośle, and PLH060029 Żurawce). The article presents the geographical-environmental description of the refuges of Natura 2000 in Roztocze, and point out their relations with the previously existing protected areas and subjects of protection.